Roles of IL-33 in Resistance and Tolerance to Systemic Candida albicans Infections - Park, Sang Jun (Immune Netw, 2016)
IL-33 is a multifunctional cytokine that is released in response to a variety of intrinsic and extrinsic stimuli. The role of IL-33 in Candida albicans infections is just beginning to be revealed. This cytokine has beneficial effects on host defense against systemic C. albicans infections, and it promotes resistance mechanisms by which the immune system eliminates the invading fungal pathogens; and it also elevates host tolerance by reducing the inflammatory response and thereby, potentially, tissue damage. Thus, IL-33 is classified as a cytokine that has evolved functionally to protect the host from damage by pathogens and immunopathology.